Pengembangan E-LKPD Jelajah Lereng Gunung Api Berbasis Deep Learning untuk Mendukung Literasi Lingkungan - Dwi Febby Mustika Ningrum; Suroso Mukti Leksono; Mudmainah Vitasari (Jurnal Studi Guru dan Pembelajaran, 2026)
This research is based on the increasing global environmental crisis, which is exacerbated by the low level of environmental literacy among students in Indonesia, a condition that is the reason for the development of contextual science learning materials oriented towards an in-depth learning approach. Accordingly, this study aims to develop an Electronic Student Worksheet (e-LKPD) entitled "Exploring Volcano Slopes," which is constructed upon deep learning principles and integrates a guided inquiry model as a strategic effort to enhance environmental literacy among junior high school students. This study employs a Research and Development (R&D) methodology, adopting the ADDIE model with implementation confined to the development stage. The procedural framework encompasses potential and problem analysis, data collection, product design, expert validation, product revision, and student response data collection. Subject selection for the expert validation and pilot testing process was based on their academic qualifications and their relevance to the field being studied. The validators included subject matter experts, media experts, and science practitioners/teachers. These validators consisted of lecturers teaching relevant subjects. Therefore, three validators from each field were appointed to obtain a broader range of perspectives, strengthen the assessment framework, and minimize potential bias in the tested product.The validity assessment yielded a score of 95%, classifying the developed product as highly valid, while the proportion of positive student responses toward the product reached 83%. The resulting e-LKPD is constructed upon three principal characteristics: (1) the utilization of the local geographic context of volcanic slope regions as a contextual foundation for learning; (2) the holistic development of environmental literacy encompassing the dimensions of knowledge, attitudes, skills, and behavior; and (3) the systematic integration of guided inquiry syntax with the foundational principles of deep learning. The findings of this study indicate that the e-LKPD "Exploring Volcanic Slopes," which was developed within the immersive learning framework, is considered valid and effective as an alternative learning material in science education and supports students' environmental literacy.